2014
DOI: 10.1055/s-0034-1383733
|View full text |Cite
|
Sign up to set email alerts
|

Old and Novel Therapies for Primary Biliary Cirrhosis

Abstract: Despite the presumed immunological pathogenesis of primary biliary cirrhosis, no clear or even harmful consequences resulted from some specific treatments addressed to modify the immunological condition. However, ursodeoxycholic acid (UDCA; 13-16 mg/kg/d) has clear favorable effects not only by improving biochemical cholestasis, but also by delaying the histological progression. Long -term treatment with UDCA is associated with excellent survival, free of transplantation in cases showing biochemical response a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 98 publications
(115 reference statements)
0
11
0
Order By: Relevance
“…In the important minority of patients with high risk, treatment unresponsive or highly symptomatic disease the need for new treatment approaches is now clear and well accepted. 149 In the setting of disease modification, evolution in our understanding of disease mechanisms is evolving rapidly into the advent of new and re-purposed therapeutics targeting key processes. Excellent opportunities are offered, in particular, by immunotherapeutic approaches targeting the upstream immune response postulated to initiate BEC injury, and by enhanced bile-acid therapies targeting the bile acid biosynthetic and feedback processes that drive 'midstream' injury to BECs.…”
Section: Targeting Pruritusmentioning
confidence: 99%
“…In the important minority of patients with high risk, treatment unresponsive or highly symptomatic disease the need for new treatment approaches is now clear and well accepted. 149 In the setting of disease modification, evolution in our understanding of disease mechanisms is evolving rapidly into the advent of new and re-purposed therapeutics targeting key processes. Excellent opportunities are offered, in particular, by immunotherapeutic approaches targeting the upstream immune response postulated to initiate BEC injury, and by enhanced bile-acid therapies targeting the bile acid biosynthetic and feedback processes that drive 'midstream' injury to BECs.…”
Section: Targeting Pruritusmentioning
confidence: 99%
“…Additionally, FXR activation increases the expression of the bilirubin and phospholipid (multiple drug resistance gene-3) export pumps, and stimulates intestinal factors such as fibroblast growth factor 19, which provide a negative feedback loop from the intestine to hepatocytes, contributing to the repression of bile acid synthesis. Preclinical studies in various animal models have demonstrated that OCA has choleretic and antifibrotic properties and metabolic effects consistent with FXR agonist effects in vivo [41] . Clinical evaluation of this new agent and phase-II efficacy and safety assessment in PBC patients have been reported [51] .…”
Section: Proposals Targeted On Cholestasismentioning
confidence: 89%
“…Fibrates Promising data on the beneficial effects of fibrates in PBC have been reported in the last 15 years, particularly by adding fibrates in patients receiving UDCA [41] . These data are summarized in table 2 .…”
Section: Proposals Targeted On Cholestasismentioning
confidence: 99%
“…50 A few clinical studies have suggested that dual therapy of budesonide (6-9 mg/day) with UDCA is more efficacious in improving the hepatic biochemical indices and histology than UDCA monotherapy in PBC subjects without concurrent cirrhosis. In one study, Leuschner et al performed a two-year prospective, controlled, double-blind study of 23 subjects undergoing dual treatment with UDCA/budesonide and 19 subjects given UDCA/placebo therapy.…”
Section: Immunomodulatory Agents Budesonidementioning
confidence: 99%